Comprehensive analysis of the cork oak (Quercus suber) transcriptome involved in the regulation of bud sprouting - Usié, Ana (2017)
Cork oaks show a high capacity of bud sprouting as a response to injury, which is important for species survival when dealing with external factors, such as drought or fires. The characterization of the cork oak transcriptome involved in the different stages of bud sprouting is essential to understanding the mechanisms involved in these processes. In this study, the transcriptional profile of different stages of bud sprouting, namely (1) dormant bud and (2) bud swollen, vs. (3) red bud and (4) open bud, was analyzed in trees growing under natural conditions. The transcriptome analysis indicated the involvement of genes related with energy production (linking the TCA (tricarboxylic acid) cycle and the electron transport system), hormonal regulation, water status, and synthesis of polysaccharides. These results pinpoint the different mechanisms involved in the early and later stages of bud sprouting. Furthermore, some genes, which are involved in bud development and conserved between species, were also identified at the transcriptional level. This study provides the first set of results that will be useful for the discovery of genes related with the mechanisms regulating bud sprouting in cork oak